Alpine skiing with total knee ArthroPlasty (ASWAP) : effects on strength and cardiorespiratory fitness - Pötzelsberger, B.; Stöggl, T.; Lindinger, S.J.; Dirnberger, J.; Stadlmann, M.; Buchecker, M.; Hofstaedter, T.; Gordon, K.; Müller, E. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study investigated the effect of a 12-week recreational skiing intervention on lower limb muscle strength and cardiorespiratory fitness in participants with unilateral total knee arthroplasty (TKA). Twenty-seven older adults (70 +/- 5 years) were assigned to the intervention (n=13) or control group (n=14) after surgery (2.5 +/- 1 years). Leg muscle strength was measured using an IsoMed 2000 dynamometer and cardiorespiratory fitness was determined by cycle ergometry before and after the intervention as well as after an 8-week retention period. The skiing intervention led to increased muscle strength in the operated leg during unilateral single joint isometric extension (maximal force: 11%; P<0.05; rate of torque development: 24%; P<0.05) and during the unilateral multi-joint isokinetic single leg strength test (8%; P<0.05). This resulted in a decreased asymmetry index in the isokinetic test (13% to 5%; P<0.05). These adaptations remained unchanged toward the retention test. No effect was observed for cardiorespiratory fitness. The results demonstrate that muscle contraction forces required during recreational skiing in individuals with TKA seem adequate and effective to increase quadriceps and hamstrings muscle strength in the initially weaker operated leg and to reduce an augmented post-operative asymmetry index.